Waiting for 2005's World Skiing Championship: an Experimental Assessment of Tourism Sustainability in Sondrio Province - Giulia Pesaro (European Regional Science Association (ERSA), 2003)
The tourism sector is more and more regarded as a central element of territorial development in many countries. According to the sustainable development approach we have to look at tourism from two possible points of view. First tourism can be regarded as a sum of economic activities playing an important role in the production of income and wealth on a territory. Second, tourists and tourism structures and activities can produce important negative externalities on the environment and the ecosystems, reducing economic benefits because of collective costs related to the depletion of the quality of the environment and the ecosystems. Moreover, the quality and the variety of the environment and the different landscapes can be considered basic factors of production of tourism. As a result, from a long term perspective, the poorest quality of the environment and of the landscape can produce e reduction in tourism activities and, consequently, of revenues. These means that the durability of tourism itself is strictly linked to the durability (or better, improvement) of the environmental quality. The sustainability of tourism is more and more discussed at international and national level but the real challenge in choosing and starting along the path of sustainable development should be searched in the local territorial levels. This is the level at which different subjects and interests really confront and dispute. And this is the level where the choose for sustainable development of tourism becomes concrete. The goal of the work is to underline the role that sustainability indicators can play in territorial decision making processes on tourism development. A methodology and a first experimental application of tourism sustainability indicators will be proposed, taking into consideration environmental and territorial costs and benefits arising from tourism activities. The experimental area is Sondrio Province, in Lombardy Region, where in year 2005 the World Nordic Ski Championship will take place. We will first suggest a possible definition for sustainable tourism in an alpine territorial area. Then, starting from a long list of possible indicators especially developed to describe the sustainability performance of tourism in the Lombardy Region, we will propose the analysis for a selection of indicators, based on available data. The aim of this working phase is the description of the sustainability of the existing tourism model. We will finally compare these results with the potential additional impacts (but also benefits) coming from public and private action needed to improve not only winter sports facilities but also accommodation capacity, access and mobility infrastructures and additional tourism services, waiting for 2005's World Championship.
Keywords: 330